EFFECT OF MEDIUM CHAIN TRIGLYCERIDE-KETOGENIC DIET ON THE LUNGS OF TYPE 2 DIABETIC MALE NEW ZEALAND RABBITS - Augustine, Banlibo Dubo; Dawud, Fatimah Alhassan; Jimoh, Abdulazeez; Umar, Ismail Alhaji (FUDMA Journal of Sciences, 2025)
Type 2 diabetes mellitus is a metabolic disorder that results in impairment of the lungs, associated with both structural and functional alterations. Ketogenic diet is a high-fat, moderate-protein and low-carbohydrate dietary regimen, with the potential of ameliorating diabetic lung complications. This study evaluated the effects of medium chain triglyceride-ketogenic diet (MCT-KD) on the lungs of type 2 diabetic male New Zealand rabbits. Type 2 diabetes was induced by feeding the rabbits formulated high fat diet for ten weeks. Twenty rabbits were divided into five groups of four rabbits each: Group I was a normoglycemic group fed with normal diet; Group II was a normoglycemic group fed with a MCT-KD; Group III was a diabetic group fed with normal diet; Group IV was a diabetic group fed with MCT-KD while Group V was a diabetic group fed with normal diet and oral administration of 4 mg/kg pioglitazone. There was a significant increase (p < 0.05) in cellular infiltration of total white blood cells, lymphocytes, neutrophils and macrophages into the bronchoalveolar lavage fluid of diabetic lungs. However, feeding with MCT-KD and administration of 4 mg/kg pioglitazone significantly decreased (p < 0.05) total white blood cells and the differential components in the diabetic lungs. The MCT-KD was observed to reduce the lung weight of the diabetic rabbits, however, no change was observed in the relative lung weight. Cellular infiltration, reduced alveolar spaces, distorted bronchial epithelium and oedema were observed in the lungs. These were observed to be alleviated after feeding with MCT-KD.